2009
DOI: 10.1002/cvde.200806729
|View full text |Cite
|
Sign up to set email alerts
|

The Aerosol‐Assisted CVD of Silver Films from Single‐Source Precursors

Abstract: Thin films of silver are deposited from tetraphenyldioxoimidodiphosphinato silver(I) [Ag{(OPPh 2 ) 2 N}] 4 Á 2H 2 O (1) and silver(I) triflouoroacetate CF 3 COOAg (2) single-source precursors (SSPs) by the aerosol-assisted (AA)CVD method. The complex (1) is a tetramer with linear and distorted tetrahedral coordination modes at silver. Two types of films, silvery and brownish, are observed from both SSPs due to the temperature gradient in the AACVD reactor. The as-deposited films are characterized by X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…As-prepared films at 480 C were of two colors; silvery film on the substrate closer to the precursor inlet, and light brownish reflective film on the adjacent substrate towards the center of the reactor. This difference is most probably caused by the temperature gradient in the reactor, or precursor decomposition as it moves through the reactor [23]. SEM of the as-deposited silvery films consists of spherical particles spreading all over the substrate surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As-prepared films at 480 C were of two colors; silvery film on the substrate closer to the precursor inlet, and light brownish reflective film on the adjacent substrate towards the center of the reactor. This difference is most probably caused by the temperature gradient in the reactor, or precursor decomposition as it moves through the reactor [23]. SEM of the as-deposited silvery films consists of spherical particles spreading all over the substrate surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Structures and ligand conformations of Ag(I) complexes containing phosphinic amide ligands have been reported [24] as well as structural characterization of some arylamidinium diphenylphosphinates forming one-, two-and three-dimensional networks by charge-assisted hydrogen bonds and through the interaction of AgSO 3 CF 3 [25]. Thin films of silver metal were deposited from tetraphenyldioxoimidodiphosphinato silver(I) [26]. The N-aminodiphenylphosphine class of compounds has been known for over 50 years [27] together with its oxidation behavior toward oxygen and sulfur [28] and the facile acidic cleavage of the P-N bond [29].…”
Section: Introductionmentioning
confidence: 99%
“…Silver has been frequently employed because of its cost‐effectiveness (if compared with gold) and its air stability (if compared with copper and nickel). Silver is usually deposited by a variety of methods such as electron beam evaporation, chemical vapor deposition (CVD),, ion beam sputtering, spin coating, electroless plating, and pulsed laser deposition . In most cases, Ag coatings exhibit a rough morphology because their growth tends to proceed by a Volmer–Weber mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, Ag coatings exhibit a rough morphology because their growth tends to proceed by a Volmer–Weber mechanism . Many silver complexes have been investigated as suitable precursors for the deposition of silver metal on metallic substrates, but only few show air and moisture stability and decomposition temperatures suitable for a convenient annealing. It was also found that, in some cases, the silver deposition that occurs by CVD may require the stabilization of the precursor by appropriate fictionalization of the ligand …”
Section: Introductionmentioning
confidence: 99%